2020
DOI: 10.1017/s1368980020004346
|View full text |Cite
|
Sign up to set email alerts
|

Are food and drink available in online and physical supermarkets the same? A comparison of product availability, price, price promotions and nutritional information

Abstract: Objective Online supermarkets are increasingly used both by consumers and as a source of data on the food environment. We compared product availability, nutritional information, front-of-pack (FOP) labelling, price and price promotions for food and drink products between physical and online supermarkets. Design For physical stores we collected data on price, price promotions, FOP nutrition labels and nutrition information from a random sample of food and drinks from six UK supermarkets. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 17 publications
1
25
0
1
Order By: Relevance
“…Lastly, we did not examine the accuracy of product information. A recent study has shown that nutrition information on the UK grocery websites was almost identical to information available in brick-and-mortar stores [ 41 ]. In accordance with the Foods and Drugs Act [ 42 ], all available product information in Canada should not have any false, misleading, or deceptive information; however, human and technical errors may still result in some mismatch of product information available on websites.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we did not examine the accuracy of product information. A recent study has shown that nutrition information on the UK grocery websites was almost identical to information available in brick-and-mortar stores [ 41 ]. In accordance with the Foods and Drugs Act [ 42 ], all available product information in Canada should not have any false, misleading, or deceptive information; however, human and technical errors may still result in some mismatch of product information available on websites.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been estimated that 85% of products found in-store in supermarkets are available online, indicating that online information is a good proxy for packaged products in physical stores. 39 Further validation work is needed to investigate similarities between online and in-store restaurant menus. Second, online nutritional information can be inaccurate.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations include the lack of nutritional composition data to analyse whether promotions are permitted or not according to the WHO Europe nutrient profile model and the lack of data on promotions in-store. Previous research from the UK has shown that, while online nutritional information and prices of products are good proxies of those found in physical stores, this was not necessarily the case for price promotions [ 1 ]. In addition, we did not collect information on the size of price promotions in the circulars, while previous research in Australia showed that price promotions on discretionary foods are larger than those on core foods [ 20 ].…”
Section: Discussionmentioning
confidence: 99%